Hunt for the Jews : Betrayal and Murder in German-Occupied Poland - Grabowski, Jan, 1962- (Book collections on Project MUSE., 2013)
Judenjagd, hunt for the Jews, was the German term for the organized searches for Jews who, having survived ghetto liquidations and deportations to death camps in Poland in 1942, attempted to hide ""on the Aryan side."" Jan Grabowski's penetrating microhistory tells the story of the Judenjagd in Dabrowa Tarnowska, a rural county in southeastern Poland, where the majority of the Jews in hiding perished as a consequence of betrayal by their Polish neighbors. Drawing on materials from Polish, Jewish, and German sources created during and after the war, Grabowski documents the involvement of the.